Development of REACT-Based Module Integrating Qurani in Temperature and Heat Materials in High School - Fitriyawany; Arusman; Putri, Madiha (Impulse: Journal of Research and Innovation in Physics Education, 2025)
This study is motivated by the limited availability of physics learning resources, which are mostly textbooks, the lack of integration of Islamic values, and the implementation of a teacher-centered education system, resulting in reduced active student participation in the learning process. The aim of this research is to determine the feasibility and practicality of developing a REACT-based module with Quranic integration on temperature and heat material in SMA/MA. This research uses a type of R&D research with a 4D model which has several stages, namely the definition stage, design stage, development stage and disseminate stage. The instruments used in this research were material expert validation sheets, media expert validation sheets, as well as interpretation expert validation sheets and questionnaires. The research results obtained from material expert validation were 94%, media expert validation was 98%, and interpretation expert validation was 93%, resulting in an overall feasibility percentage of 95% with very feasible criteria, as well as practical results obtained from student responses. amounting to 88% with very practical criteria. It can be concluded that the REACT-based module with Quranic integration in temperature and heat material in SMA/MA is very feasible and very practical to use in the learning process.